Justice spending in England and Wales - Magdalena Dominguez; Ben Zaranko (Institute for Fiscal Studies (IFS), 2025)
The justice system is an important part of how the government upholds the law and maintains public order, making it a significant area of responsibility. In England and Wales, the Ministry of Justice (MoJ) is responsible for funding and overseeing most functions of the justice system, including the courts and tribunals system, the judiciary, prisons, the probation service and legal aid. The department's responsibilities do not include the police (this lies with the Home Office), and both the Crown Prosecution Service and Serious Fraud Office sit separately as nonministerial departments, but spending by the MoJ can be thought of, to a first approximation, as spending on the justice system of England and Wales. In this report, we provide a detailed description and analysis of how MoJ spending has evolved over more than two decades. This provides key context ahead of the Spending Review due later in 2025, and ahead of a new programme of work at the Institute for Fiscal Studies on the economics of the justice system.
Keywords: 330; Government finances and spending; Justice; Justice system; Government spending; Public sector